(untitled) (Revista Brasileira Multidisciplinar, 2026)
The Dental Specialties Centers represent reference units for primary care and are a continuity of care, offering the population specialized treatment in several areas of dentistry. The aim of this study was to evaluate the total number of procedures in the area of endodontics in a DSC located in the city of João Pessoa, Paraíba, Brazil. A cross-sectional study was carried out, using secondary data at the Cruz das Armas Dental Specialty Center (CADC). The data covers the period from January 2010 to June 2022, available on DATASUS and evaluated from a descriptive statistical analysis. Most patients treated were female, representing 62% of the total, and the predominant age group was adults (30-59 years). Most of the patients attended reside in the micro-region of João Pessoa. The average number of endodontic procedures shows that 2010 had the best performance with an average of 86.58 procedures per month. Monthly production has been decreasing and becoming insufficient to reach the target established by ministerial ordinance. Self-analysis and monitoring are necessary in order to identify weaknesses in the service and establish strategies to change reality.